Performance of Turkeys in Enrichment Environment with Perches and Outdoor Access under Tropical Conditions - González-Zapata, FA; Itza Ortiz, Mateo Fabian; Piñero-Vazquez, Angel; Sangines Garcia, JR; Velázquez-Madrazo, PA; Bello-Pérez, EV; hay-Canul, AJ; Aguilar-Urquizo, Edgar (2022)
Heat stress compromises turkey’s productivity and increase mortality mainly in the final stages of growth. This study evaluated the effect of perches and its interaction with outdoor access on turkey performance in high environment temperature humidity index (THI). Turkeys were reared in 1.75 × 5 m indoor floor pens and were fed with a standard commercial diet, offered ad libitum according to the productive phase. All poults were housed indoors until 62 d of age. A free-range area for a replicate of 8.75 m2, with natural shadow, was available from 07:00 to 19:00 h. Final density was 10.33 ± 0.22 kg/m2. The treatments were a combination of a factorial arrangement (2 × 2) with or without perches and, with or without access to the outdoors. From 10:00 and 19:00 THI was above critical level of comfort (heat stress). In indoors turkeys, feed intake (FI) decreased, and water intake increased, panting was observed, and had a significantly lower final body weight (BW) and FI than turkeys allowed outdoors (p<0.05). Perch availability decreased final BW and FI (p<0.05). Differences in weight of breast meat, wings, or thighs between treatments were negligible. In conclusion turkeys with outdoor access from 62 d of age had better performance.